Predictors of Bullying among 10 to 11 Year Old School Students in Australia - Burns, Sharyn; Cross, D.; Alfonso, H.; Maycock, Bruce (The Clifford Beers Foundation in collaboration with the University of Maryland School of Medicine, 2008)
Cross-sectional data collected at baseline from the Grade 6 cohort of the Friendly Schools, Friendly Families Project (n = 1,257) were analysed to investigate differences in self-reported attitudes and behaviours of students who reported bullying regularly and occasionally compared with those who reported never bullying others. This study found some similarities and some differences between students who reported bullying regularly and those who reported bullying occasionally, supporting the need to consider both groups when developing school-based bullying interventions. Attitudes to bullying, social and emotional health, peer support and being bullied were predictors of both regular and occasional bullying. The findings of this study support the need for universal bullying prevention interventions targeting the whole school community, including specific selective and indicated strategies, to effect a change in bullying behaviours.